Hierarchical CdS/m-TiO2/G ternary photocatalyst for highly active visible light-induced hydrogen production from water splitting with high stability - Lu, Yi; Cheng, Xiu; Tian, Ge; Zhao, Heng; He, Li; Hu, Jie; Wu, Si-Ming; Dong, Ying; Chang, Gang-Gang; Lenaerts, Silvia; Siffert, Stephane; Van Tendeloo, Gustaaf; et al. (Nano Energy, 2018)
Hierarchical semiconductors are the most important photocatalysts, especially for visible light-induced hydrogen production from water splitting. We demonstrate herein a hierarchical electrostatic assembly approach to hierarchical CdS/m-TiO2/G ternary photocatalyst, which exhibits high photoactivity and excellent photostability (more than twice the activity of pure CdS while 82% of initial photoactivity remained after 15 recycles during 80 h irradiation). The ternary nanojunction effect of the photocatalyst has been investigated from orbitals hybrid, bonding energy to atom-stress distortion and nano-interface fusion. And a coherent separation mechanism of charge carriers in the ternary system has been proposed at an atomic/nanoscale. This work offers a promising way to inhibit the photocorrosion of CdS and, more importantly, provide new insights for the design of ternary nanostructured photocatalysts with an ideal heterojunction.
Created from Fastlane, Scopus look-up
Keywords: CdS; Graphene sheets; Mesoporous TiO; Ternary photocatalysis; Visible light-induced water splitting